0
$\begingroup$

Suppose that that random variable $N$ follows a Poisson distribution with mean $\lambda=6$. Suppose that the conditional distribution of the random variable $X$, given that $N=n$, follows that of a $Binomial(n,0.6)$.

Find the Joint Moment Generating Function of $(N, X)$.

Initially I just tried to use the definition. I found the joint PMF using the definition of the conditional distribution, but then I have to sum over both of them in order to find the joint MGF, and this was the step I was stuck at because trying to do a double sum over the product of the binomial and Poisson PMFs doesn't exactly go over very nicely.

Since this problem does NOT assume independence, I can't exactly attempt to use that to my advantage either... so now I'm stuck. How can I calculate this joint MGF?

$\endgroup$
  • $\begingroup$ Start with the definition of joint mgf: $M_{N,X}(s,t) = E[e^{sN + tX}]$. Next you try to take a double expectation, conditional on $N$. $\endgroup$ – BGM Feb 5 '18 at 17:03
0
$\begingroup$

The summations are doable. The joint pmf is $$f_{X, N}(k, n) = \operatorname P(X = k \mid N = n) \operatorname P(N = n) = \binom n k p^k (1 - p)^{n - k} e^{-\lambda} \frac {\lambda^n} {n!}.$$ Sum over $k$ first: $$\sum_{k = 0}^n e^{s k + t n} f_{X, N}(k, n) = e^{-\lambda} \frac {\lambda^n} {n!} e^{t n} \sum_{k = 0}^n \binom n k (p e^s)^k (1 - p)^{n - k} = \\ e^{-\lambda} \frac {\lambda^n} {n!} e^{t n} (p e^s + 1 - p)^n.$$ Then sum over $n$: $$\operatorname E\left[ e^{s X + t N} \right] = \sum_{n=0}^\infty \sum_{k = 0}^n e^{s k + t n} f_{X, N}(k, n) = \\ e^{-\lambda} \sum_{n=0}^\infty \frac {(\lambda e^t (p e^s + 1 - p))^n} {n!} = \\ \exp( -\lambda + \lambda e^t (p e^s + 1 - p)).$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.